Studi literatur: pemanfaatan teknologi biogas dari limbah organik di Indonesia - Fauziah, Lulu Hani; Hidayatullah, Ahmad Fauzan (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
The need for energy resources is increasing every year. Meanwhile, reserves of fossil energy sources are decreasing and will run out over time, such as coal, oil and natural gas. The contribution from the burning of oil and natural gas causes emissions that can pollute the earth. Biogas is a renewable energy. environmentally friendly and has the opportunity to be developed as an alternative energy that is starting to be taken into account. In this case the government is trying to develop renewable energy throughout Indonesia as stated in Government Regulation Number 79 of 2014 concerning National Energy Policy. This qualitative research aims to determine the use of biogas in Indonesia taken from various studies in several regions in Indonesia by reviewing previous studies to provide additional explanations about the obstacles and solutions to biogas development in Indonesia.